2013
DOI: 10.1371/journal.pone.0061727
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of LED Fluorescence Microscopy for Diagnosis of Pulmonary and HIV-Associated Tuberculosis in a Hospital Setting in Indonesia

Abstract: BackgroundFluorescence microscopy (FM) has not been implemented widely in TB endemic settings and little evaluation has been done in HIV-infected patients. We evaluated diagnostic performance, time and costs of FM with light-emitting diodes technology (LED-FM), compared with conventional (Zieh-Neelsen) microscopy in a hospital in Indonesia which acts as referral centre for HIV-infected patients.MethodWe included pulmonary tuberculosis suspects from the outpatient and HIV clinic. Direct and concentrated sputum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 17 publications
(21 reference statements)
2
19
0
Order By: Relevance
“…Nonetheless, SROC plots suggested that liquid culture reference standard was associated with higher diagnostic accuracy of LED-FM (see online supplementary material). Studies using culture on one specimen (n=7) [14-17, 19, 22, 23] had a lower pooled specificity (94.7%) and a higher sensitivity (70.0%) compared with studies using more than one specimen (n=6) [13,15,18,20,21,24] (98.5% and 61.1%, respectively), although the differences were not statistically significant. SROC plots suggested that culture reference based on more than one specimen improved the diagnostic accuracy of LED-FM, although associated with increasing heterogeneity in both sensitivity and specificity estimates of the LED-FM (see online supplementary material).…”
Section: Subgroup Accuracy Analysismentioning
confidence: 93%
See 4 more Smart Citations
“…Nonetheless, SROC plots suggested that liquid culture reference standard was associated with higher diagnostic accuracy of LED-FM (see online supplementary material). Studies using culture on one specimen (n=7) [14-17, 19, 22, 23] had a lower pooled specificity (94.7%) and a higher sensitivity (70.0%) compared with studies using more than one specimen (n=6) [13,15,18,20,21,24] (98.5% and 61.1%, respectively), although the differences were not statistically significant. SROC plots suggested that culture reference based on more than one specimen improved the diagnostic accuracy of LED-FM, although associated with increasing heterogeneity in both sensitivity and specificity estimates of the LED-FM (see online supplementary material).…”
Section: Subgroup Accuracy Analysismentioning
confidence: 93%
“…12 articles [13][14][15][16][17][18][19][20][21][22][23][24], reporting 12 independent studies, were included in the meta-analysis. One study [15] had two different patient groups (group 1: unlikely HIV-infected; group 2: HIV-infected) with separately analysed data. We considered these two patient groups to be independent in the meta-analysis.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations